2004
DOI: 10.1080/09638280410001704322
|View full text |Cite
|
Sign up to set email alerts
|

Pharynx and oesophagus evaluation during the swallow using helical computerized tomography

Abstract: This study shows that HCT enables visualization of TP of PES complementing VF or endoscopic swallowing studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 8 publications
1
12
0
1
Order By: Relevance
“…Ohmae et al 13 also demonstrated that head rotation results in lateralization of the bolus. Moreover, Takehara and Chu 19 reported that head rotation closes the piriform sinus on the rotated side, causing food to fl ow down the opposite side of the pharynx.…”
Section: Comparison Between Head-on and Head-rotated Viewsmentioning
confidence: 98%
See 2 more Smart Citations
“…Ohmae et al 13 also demonstrated that head rotation results in lateralization of the bolus. Moreover, Takehara and Chu 19 reported that head rotation closes the piriform sinus on the rotated side, causing food to fl ow down the opposite side of the pharynx.…”
Section: Comparison Between Head-on and Head-rotated Viewsmentioning
confidence: 98%
“…However, the lower piriform sinus did not respond in the same manner. This notion that the piriform sinuses close upon rotation is based on data collected via videofl uoroscopy 11 and endoscopy; 19 therefore, these previous studies were not able to observe the lower piriform sinus directly. Our results suggest that the upper piriform sinuses play a more important role in food fl ow, whereas the lower piriform sinuses do not show the same degree of morphological change.…”
Section: Comparison Between Head-on and Head-rotated Viewsmentioning
confidence: 99%
See 1 more Smart Citation
“…Imaging of the closure of the hemipharynx with head rotation [16] and swallowing analysis using a single-slice cine mode [17] have also been reported. However, in these techniques, scanning is carried out with the subject in the supine position and the analysis involves only axial images.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies using VFSS and a manometer demonstrated that head rotation lateralizes the bolus away from the direction of head rotation and reduces upper esophageal sphincter pressure [1][2][3]. Several studies using CT and endoscopy have demonstrated morphologic change of the lower pharynx in the head-rotated posture [4][5][6][7][8]. Takasaki et al [4,5] observed the piriform sinuses using an endoscope and stated that head rotation may cause changes in the anatomical relationship between the laryngeal cartilages and the hypopharyngeal wall, resulting in differences in the size of the piriform sinus between the 2 sides.…”
Section: Discussionmentioning
confidence: 99%